2018
DOI: 10.1080/09540105.2018.1439454
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-inflammatory activity of the Artemisia montana leaf ethanol extract in macrophage RAW 264.7 cells

Abstract: Artemisia is one of the largest genera of the family Asteraceae or Compositae, consisting of 500 species. Some Artemisia species, such as Artemisia afra, A. sacrorum, and A. annua, have been widely used as traditional medicine to treat inflammatory and malarial diseases. However, the biological activity of A. montana has not been broadly studied. Therefore, in this study, we investigated the anti-inflammatory activity of A. montana leaf extract (ALE) and its molecular mechanisms in lipopolysaccharideactivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“… 32 Previous studies on the anti-inflammatory of Artemisia species were stated. Testing extract of A. annua , 33 A. fukudo , 34 and A. montana 35 on murine RAW 264.7 macrophage cells showed anti-inflammatory activity by inhibiting LPS-induced nitric oxide and prostaglandin E 2 productions. Our A. lactiflora extract might also have those similar anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 92%
“… 32 Previous studies on the anti-inflammatory of Artemisia species were stated. Testing extract of A. annua , 33 A. fukudo , 34 and A. montana 35 on murine RAW 264.7 macrophage cells showed anti-inflammatory activity by inhibiting LPS-induced nitric oxide and prostaglandin E 2 productions. Our A. lactiflora extract might also have those similar anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 92%
“…Macrophages are known to play a critical role in innate immunity and attack, destroy and ingest foreign substances by producing cytokines and NO (Jeong, Kim, & Min, 2018). In this study, we investigated the immuno-stimulatory effects of L-EPS on RAW264.7 cells by examining the phagocytic activity and the production of NO and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The present research showed that the extract of Artemisia fruit contains flavonoids, which capture free radicals (Andriantsitohaina, 1999, Baumann et al, 1980 and many other active compounds which activate the enzymes and transporter proteins in the membrane of the cell (Kotani et al, 2000). Since Artemisia has better phytochemical compounds (Kooti et al) which may have role in more activities (Jeong et al, 2018, Vijeesh et al, 2017. Moreover, this study showed the difference between hot and cold extract of Artemisia fruit.…”
Section: Resultsmentioning
confidence: 71%